Algae in the diete of quails - Yunusov, H.B.; Khodjaeva, N.D.; Ummatov, U.; Khujaeva, N.; Buranova, K. (E3S web of conferences, 2024)
In this work, the subject of research was a microscopic algae – chlorella and a higher aquatic plant – duckweed. The most optimal variants of nutrient media for algae cultivation have been studied. It is proposed to cultivate chlorella on a nutrient medium “04” based on farm wastewater and farm wastewater for duckweed. The influence of algae biomass (chlorella and duckweed) on the growth and development of quails has been studied. It is proposed to include quails in the diet as a dietary supplement to the main feed Chlorella vulgaris and Lemna minor L, which will improve zootechnical and economic indicators, has a positive effect on increasing live weight, egg production and viability.